Correlation between time lag of arterial–plethysmographic waveforms and systemic vascular resistance: a prospective study. (2nd January 2018) - Muthuchellappan, Radhakrishnan; V. J., Ramesh; Ganne S., Umamaheswara Rao; K., Thennarasu; Jacob, Anjana; G., Sripathy; V., Bhadrinarayan; K., Mohanvelu
Abstract: Blood pressure (BP), a surrogate of cardiac output (CO), is also dependent on systemic vascular resistance (SVR). But SVR is not routinely monitored in daily clinical practice. We hypothesise that the time difference between the peripheral arterial waveform and the finger plethysmographic waveform (time lag index - TLi) could indicate the systemic vascular resistance. In this study, we correlated TLi with the systemic vascular resistance measured by minimally invasive CO monitor (pulse contour analysis). SVR changes in response to administration of mannitol were studied. American Society of Anesthesiologists (ASA) class I and II patients undergoing major intracranial surgeries were recruited. Arterial cannulation and pulse-oximetry recordings were done in the same limb. Arterial and plethysmographic waveforms were recorded before mannitol infusion (baseline) and at every 10 minutes for 60 minutes after the termination of mannitol infusion. Simultaneously, SVR was recorded from the Vigileo FLotrac CO monitor. Using custom-made programme, the time difference between both waveforms was calculated and corrected for heart rate (TLi). The correlation between time lag and the systemic vascular resistance was assessed using a mixed effect model, adjusting for the subject. Data of one hundred subjects were analysed. Following mannitol administration, there was a significant decrease in the SVR and the TLi ( p  < .001). The patient characteristics influenced both the baseline values of SVR (intercept) and the changes in SVR over time (slope). As both the baseline value and the change over time for SVR were different in each patient, we used mixed effect model analysis to assess the relationship between SVR and TLi for different time periods. The effect of TLi on SVR was significant ( β  = 877.16, p  = .008). The high beta coefficient suggests that when SVR increases, the TLi also increase and vice versa. A strong correlation between SVR and TLi was demonstrated for a given patient. Further studies are needed to explore the possibility of utilising this parameter to follow up changes in SVR in an individual patient at a particular point in time in different clinical scenarios.